Pengujian Mesin Pendingin Minuman Portable Kapasitas 4,7 Liter Dengan Modul Termoelektrik Menggunakan Aluminium Dan Tanpa Aluminium - G, Renhard Niptro; Mainil, Rahmat Iman; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Thermoelectric cooling is a heat pump equipment based works on peltier effect. When electric current was applied, the heat absorption occurs at the junction of the two metals and heatloss in another connection. The Benefits of using thermoelectrics could be applied via a portable beverage cooler. Therefore, the portable beverage cooler test using 1 peltier element TEC1-12706 type with capacity of cooler box is 4,7 liter. Cooler box dimensions arelength 24,7 cm, width 18,5 cm and height 18,5 cm. The data capture in this study are cooling chamber temperature, heat sink temperature, ambient temperature, the temperature of the inner wall and outer wall. The results show that steady temperature conditions are using of aluminum without cooling load 21°C after 45 minutes and a load of six beverage cans (1980 ml) 27,8°C after 50 minutes. Whereas a portable beverage cooler isn’t using ofaluminum without cooling load 24,6°C after 50 minutes and a load of six beverage cans (1980 ml) 27,7°C after 35 minutes. A portable beverage cooler is using aluminum has a better performance than a portable beverage cooler isn’t using aluminum.The greater cooling load then be longer performance of steady temperature. Whereas not the use of aluminum inversely.Keywords: Thermoelectric, Cooling Loads, Steady, Aluminium